2009
DOI: 10.1161/circoutcomes.108.830398
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study to Identify Barriers to Local Implementation of Prehospital Termination of Resuscitation Protocols

Abstract: Background— Despite the existence of national American Heart Association guidelines and 2 termination-of-resuscitation (TOR) rules for ceasing efforts in refractory out-of-hospital cardiac arrest, many emergency medical services agencies in the United States have adopted their own local protocols. Public policies and local perceptions may serve as barriers or facilitators to implementing national TOR guidelines at the local level. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Results from focus groups at the NAEMSP annual meeting demonstrated three groups whose policies have created barriers to implementation of TOR protocols: payers that incentivize transport, legislators that mandate prehospital resuscitation, and community expectations that EMS will transport for resuscitation. 26 In addition, within the EMS community, the prevalent "rescue culture" of EMS providers and concerns about liability have also been barriers to implementation of TOR protocols. 26 In a study on barriers to removing pediatric intubation from an EMS system, Youngquist et al found that the most common reasons for barriers to change were a feeling that ".…”
Section: Ems Systems Following Termination-of-resuscitation Guidelinesmentioning
confidence: 99%
“…Results from focus groups at the NAEMSP annual meeting demonstrated three groups whose policies have created barriers to implementation of TOR protocols: payers that incentivize transport, legislators that mandate prehospital resuscitation, and community expectations that EMS will transport for resuscitation. 26 In addition, within the EMS community, the prevalent "rescue culture" of EMS providers and concerns about liability have also been barriers to implementation of TOR protocols. 26 In a study on barriers to removing pediatric intubation from an EMS system, Youngquist et al found that the most common reasons for barriers to change were a feeling that ".…”
Section: Ems Systems Following Termination-of-resuscitation Guidelinesmentioning
confidence: 99%
“…When a research question would best involve qualitative research methods and a study is conducted according to these standards, this journal would welcome this approach. 8,9 Qualitative research is defined by a substantial body of literature from multiple disciplines [10][11][12][13][14][15] and has been applied in the study of health and health care since the mid-1990s. …”
mentioning
confidence: 99%
“…When a research question would best involve qualitative research methods and a study is conducted according to these standards, this journal would welcome this approach. 8,9 Qualitative research is defined by a substantial body of literature from multiple disciplines [10][11][12][13][14][15] and has been applied in the study of health and health care since the mid-1990s. 15,16 The methods can be used to understand complex social processes, organizational change, individual health behaviors, and nuanced aspects of environmental context that influence quality of care, healthcare delivery, and health outcomes for individuals and populations.…”
mentioning
confidence: 99%
“…Examples include articles that report on randomized trials, 1,2 cross-sectional studies, 3 observational cohort studies, 4 economic analyses, 5-7 meta-analyses, 8 systematic reviews, 9,10 prepost designs, 11 simulations, 12 and qualitative research. 13,14 A glance at this content quickly dispels the myth that outcomes research is primarily associated with secondary data analyses and data mining. That type of work, for the appropriate questions and with the appropriate methodological approach, can make important contributions, but is hardly the only study design used by the field.…”
mentioning
confidence: 99%